DEVELOPING REGIONAL COMPETITIVENESS BASED FISHERY HARBOUR LANDING FISH (PPI) PEUDADA BIREUEN DISTRICT-ACEH - Umuslim, Rahmad (JURNAL KEBANGSAAN, 2016)
Geographically Bireuen known as the golden triangle region of Acehs economy because it is located in the central province of Aceh . Most of the district is a coastal region with the support of several Fish Landing Base (PPI), which became the base supporting sectors of the regional economy. PPI Peudada is the largest, and its existence is important to develop the local economy. And can spearhead Locally Generated Revenue (PAD) in Bireuen. The purpose of this study was to determine the existence of PPI Peudada the supporting sectors of the economy and into alternative community income, and to determine the development of regional competitiveness based fishery. Results of the study became the basis for local authorities to issue a new policy in implementing the new economic region in Bireuen, administratively birth of favorable policies of the fishermen, businesses and regions in the development of his attempt. In terms of economic policy and its implementation affect the original reception area of the fisheries sector, and will open up new employment opportunities for the community and the surrounding region PPI Peudada . Keywords: Fisheries, PPI, Regional Competitiveness